Chlorogenic acid supplementation alleviates dextran sulfate sodium (DSS)-induced colitis via inhibiting inflammatory responses and oxidative stress, improving gut barrier integrity and Nrf-2/HO-1 pathway. (December 2021) - Wan, Fan; Cai, Xueying; Wang, Mengyu; Chen, Liang; Zhong, Ruqing; Liu, Lei; Yi, Bao; Hou, Fujiang; Zhang, Hongfu
Graphical abstract: Highlights: CGA supplementation can enhance antioxidant capacity in DSS-induced colitis mice. CGA supplementation can activate Nrf-2/HO-1 pathway in DSS-induced colitis mice. CGA supplementation can improve gut barrier integrity in DSS-induced colitis mice. Abstract: Chlorogenic acid (CGA) is an important source of phenolic acids with multiple health functions such as antioxidation, anti-inflammation, and free radical scavenging effects. This study aimed to investigate whether the nuclear factor erythroid 2-related factor 2 (Nrf-2)/HO-1 pathway played a role in CGA ameliorating DSS-induced colitis in mice. 500 mg/kg CGA (high chlorogenic acid, HCGA) and 250 mg/kg CGA (low chlorogenic acid, LCGA) supplementation could alleviate the symptoms of colitis and the related mechanisms. qPCR results indicated that HCGA treatment dramatically upregulated mRNA expression levels of anti-inflammatory cytokine, antioxidative enzymes, occluding, and Nrf-2/HO-1 pathway downstream targets. Western blot results proved that HCGA supplementation significantly upregulated HO-1 level. Besides, Spearman's correlation analysis showed that the colon mRNA expression levels of antioxidative enzymes had a positive correlation with Nrf-2/HO-1 pathway downstream targets. Collectively, CGA supplementation could effectively ameliorate DSS-induced colitis by activating the Nrf-2/HO-1 pathway to suppress oxidative stress and inflammatory responses, and promoting gut barrier.